Airflow patterns through a sliding door during opening and foot traffic in operating rooms. (15th November 2016) - Villafruela, J.M.; San José, J.F.; Castro, F.; Zarzuelo, A.
Abstract: It is common practice for operating rooms (OR) to have more pressure than the adjacent enclosures. This is to prevent the entry of potentially contaminated air and the consequent risk of wound infection. However, when the OR door is opened the pressure difference between the two areas disappears and can cause containment failures. If a person enters or leaves the OR during door operation, additional perturbations are also generated in the airflow pattern in the doorway. In this paper, instantaneous airflows are measured during the passage of a person through a sliding door in a real OR with the HVAC system working under operating conditions. An ultrasonic anemometer that measures the magnitude and direction of the instantaneous air velocity in the doorway is used. Results show that, even though the OR has a sliding door and an initial overpressure of 20 Pa, together with what is, a priori, a good HVAC system control strategy, a small volume of air enters the OR during a cycle of door opening and closing even without the passage of a person. Furthermore, if a person walks through the door the volume of air entering the OR is higher, especially if the person enters the OR. Highlights: Human motion affects airflows through a real OR door. We determine spatial and temporal distribution of airflow through a real OR door. Ultrasonic anemometry enables accurate quantification of airflow across the doorway. Despite overpressure there is incoming air into the OR.